The enzyme encoded by Myrmecia incisa, a green microalga, phospholipase A2 gene preferentially hydrolyzes arachidonic acid at the sn-2 position of phosphatidylcholine - Lin, Mei-Zhi (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024. Published by Elsevier Masson SAS.